Clinical Presentation, Outcomes, and Treatment of Membranous Nephropathy after Transplantation - Artur Q. B. da Silva; Taina V. de Sandes-Freitas; Juliana B. Mansur; Jose Osmar Medicina-Pestana; Gianna Mastroianni-Kirsztajn (International Journal of Nephrology)
There are scarce data about clinical presentation and outcomes of posttransplant membranous nephropathy (MN), and few reports include a large number of patients. This was a retrospective cohort including adult patients with posttransplant MN transplanted between 1983 and 2015 in a single center (n=41). Only patients with histological diagnosis of MN in kidney grafts were included. Clinical and laboratory presentation, histological findings, treatment, and outcomes were detailed. Patients were predominantly male (58.5%), with a mean age of 49.4 ± 13.2 years; 15 were considered as recurrent primary MN; 3 were class V lupus nephritis; 14 were considered as de novo cases, 7 secondary and 7 primary MN; and 9 cases were considered primary but it was not possible to distinguish between de novo MN and recurrence. Main clinical presentations were proteinuria (75.6%) and graft dysfunction (34.1%). Most patients with primary recurrent and de novo primary MN were submitted to changes in maintenance immunosuppressive regimen, but no standard strategy was identified; 31 patients presented partial or complete remission, and glomerulopathy appeared not to impact graft and patient survival.